A Comprehensive Systematic Review of The Relationship between Breathing Exercises (Yoga / Pranayama) and Lung Function in Asthma Patients - Harlina Hi M Konoras; Muhammad Irsan; Brian Enrique Fritzgerald (The International Journal of Medical Science and Health Research, 2026)
Introduction: Asthma is a chronic inflammatory airway disease characterized by variable airflow obstruction, affecting millions worldwide. Despite pharmacological advances, many patients experience suboptimal control and seek complementary therapies. Breathing exercises, including yoga and pranayama, have been widely advocated as adjunctive interventions to improve respiratory mechanics and lung function in asthma (Santino et al., 2020). This systematic review comprehensively examines the relationship between structured breathing exercises and objective lung function parameters in asthma patients. Methods: A systematic review was conducted following a detailed screening protocol. Studies were included if they involved ≥80% asthma patients or provided subgroup analysis, examined yoga/pranayama/structured breathing techniques, measured objective lung function (e.g., FEV1, FVC, PEFR), employed controlled study designs (RCTs, quasi-experimental, cohort, case-control, systematic reviews), included a comparison group, and had an intervention duration of at least one week. Data extraction covered intervention details, lung function assessments, study design, population characteristics, outcomes, and contextual factors from 80 included sources. Results: The evidence reveals heterogeneous findings. Meta-analyses showed conflicting results; for example, Yang et al. (2016) found no significant effect on FEV1 (MD 0.04 L, 95% CI -0.10 to 0.19), while Rathore et al. (2025) reported a significant improvement (WMD 0.47 L, p<0.00001). PEFR demonstrated the most consistent improvements across studies (e.g., Cramer et al., 2014: SMD 0.49, p<0.001). Pranayama and Buteyko techniques showed comparable efficacy, with some evidence favoring Buteyko for certain spirometric parameters (Swathi et al., 2021; Elsaid et al., 2023). Improvements were more pronounced with supervised, frequent (daily), and longer-duration (≥8 weeks) interventions, particularly in adult mild-to-moderate asthma populations. Discussion: The heterogeneity in outcomes can be attributed to variations in study quality, intervention type, duration, intensity, population characteristics, and cultural context. High-quality RCTs often reported more modest lung function benefits alongside significant improvements in symptoms and quality of life. The primary mechanism likely involves enhanced respiratory muscle efficiency, improved breathing pattern control, and potential modulation of autonomic and inflammatory pathways, rather than fundamental reversal of airway obstruction. Conclusion: Breathing exercises, particularly yoga and pranayama, can serve as beneficial adjunctive therapy for asthma, primarily improving PEFR and potentially FEV1 with sustained practice. They are most effective for adults with mild-to-moderate asthma when practiced regularly under guidance. Future research should prioritize high-quality, large-scale RCTs with standardized protocols, longer follow-up, and exploration of mechanisms and cost-effectiveness to solidify clinical recommendations.